Optimizing Learning Quality: A Total Quality Management Approach in Islamic Secondary Schools - Siti Zainab; Poppy Rachman; Arifia Retna Yunita (Al-Qalam Institue, 2026)
This study aims to examine the implementation of Total Quality Management (TQM) in improving the quality of learning in an Islamic junior secondary school. A descriptive qualitative approach was employed, with data collected through interviews, observations, and documentation. The participants included the principal, teachers, and administrative staff. The findings indicate that TQM implementation established a systematic framework for learning quality improvement through participatory planning, continuous supervision, regular evaluation, and consistent follow up actions. The active involvement of teachers in planning, monitoring, and professional development contributed to enhanced teaching competencies and more effective learning processes. In addition, the successful implementation of TQM was supported by a strong organizational culture characterized by religious values, collaborative decision making, and a commitment to continuous improvement embedded in academic and character building programs. These findings imply that TQM provides an effective management framework for fostering sustainable improvements in learning quality by strengthening institutional commitment, teacher professionalism, and a culture of continuous quality enhancement in Islamic educational institutions.